Promotion of Ramie Fibre Crop in Jhum Fallow Area of Wokha District in Nagaland-A New Initiative - Ray, Sanjay Kumar; Baishya, S. K.; Baishya, L.K.; Rajkhowa, D.J. (Indian Journal of Hill Farming, 2019)
Ramie (Boehmeria nivea L.) is recognized as the strongest and longest natural fibre having manifold uses. The field experiment was conducted in 2 villages covering an area of 6 ha under the frontline demonstration (FLD) during 2014-2017 to assess the performance potential and productivity of ramie (variety-Hazarika) in the jhum fallow lands of Wokha district in Nagaland. The training cum demonstration programme was conducted on the package of practices of ramie cultivation before initiation of the experiment in the farmer’s field. A total of 3, 60,000 numbers of ramie plantlets was planted in farmers participatory approach to cover an area of 6 ha. The result of the demonstration revealed that the ramie performed very well in jhum fallow lands and yield ranged from 16.21 to 18.15 q/ha/year. The average cost of ramie cultivation during the study period was Rs. 18,500/ha. The economic analysis of ramie cultivation revealed an average net annual income of Rs. 39,918 /ha with a B: C ratio of 3.16:1. From the study, it can be concluded that fibre production through the introduction of ramie is not only a viable options for jhumias for income enhancement but also it helps to manage jhum fallow land in a sustainable manner.